Synthesis of palm oil-based fatty methylhydrazide - Al-Mulla, Emad A. Jaffar; Ibrahim, Nor Azowa; Al-Karkhi, Isam Hussain T.; Shameli, Kamyar; Zidan, Mohammed; Ahmad, Mansor; Wan Yunus, Wan Md. Zin (Springer Netherlands, 2013)
Fatty methylydrazides (FMHs) have been successfully synthesized from palm oil. Glycerol was produced as a by-product. The synthesis was carried out by reﬂux palm oil with methylhydrazine in hexane. FMHs have been characterized using elemental analysis, Fourier transform infrared spectroscopy and 1H nuclear magnetic resonance technique. The results showed that a 6:1 molar ratio of palm oil to methylhydrazine, a round 78 % maximum conversion of palm oil into FMHs and a 10 h reaction time are the optimum reaction conditions.